Employee Performance Transformation through Organizational Culture and Communication Innovation at PT. Alam Jaya Karawang - Rohmah, Siti; Nandang, Nandang; Apriani, Zenita (Lembaga Riset dan Inovasi Al-Matani, 2024)
The purpose of this study is to explore the impact of organizational culture and organizational communication on employee performance at PT Alam Jaya Karawang. This study uses a verification method with quantitative data analysis, distributing questionnaires as a data collection tool to employees of PT Alam Jaya Karawang. The findings in this study are that organizational culture has a partial influence on the performance of employees of PT Alam Jaya Karawang with a tcount value greater than the t valuetabel (18.696> 1.655). Organizational communication also has a partial influence on the performance of employees of PT Alam Jaya Karawang with a tcount value greater than the t valuetabel (12.731> 1.655). Simultaneously, organizational culture and organizational communication have an influence of 81% on the performance of employees of PT Alam Jaya Karawang while the remaining 19% can be attributed to other factors not examined in this study.